Reproductive performance of sows inseminated once or twice using semen stored in kiew extender - Silveira, Paulo Roberto Souza da; Wentz, Ivo; Freitas, Alfredo Ribeiro de (Pesquisa Agropecuaria Brasileira, 2014)
The trial was conducted at Concórdia - SC, Brazil, from April to December 1979 in order to evaluate viability of semen preserved in the Kiew diluent. The semen was stored at 15°C for 72 hours, Six hundred and ninety-four sows and gilts were inseminated with semen from ten boars. A total of 151 females were inseminated once, 24 ± 7 hours after the beginning of the estrus and the other 543 received a double insemination during the same estrus period with an eight to twelve - inter - val between time two inseminations. Of all females inseminated 83% had a litter size average of 10.56 and 10.20 piglets born alive per litter. Females inseminated twice during estrus showed an increase of 2.32% in the farrowing rate and 8.05% in the litter size average. The difference in litter size was significant (P<0.05). The farrowing rate and the litter size differences were not significant (P>0.05) either by use of single or double insemination for primiparous sows. Pluriparous sows farrowing rate and average litter size were 83.77% and 11.38 vs. 80.56% and 10.24, for double and single insemination, respectively. Only the litter size differed significantly (P<0.05). It was concluded that semen storage for three days in kiew extender is feasible ensuring high farrowing rates and litter size. The litter size was increased by the use of double insemination during the estrus period of pluriparous sows.